2021
DOI: 10.1038/s41598-021-88294-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of CT-derived myocardial strain measurement in patients with advanced cardiac valve disease

Abstract: To explore the feasibility of CT-derived myocardial strain measurement in patients with advanced cardiac valve disease and to compare it to strain measurements derived from transthoracic echocardiography (TTE). 43 consecutive patients with advanced cardiac valve disease and clinically indicated retrospectively gated cardiac CTs were retrospectively analyzed. The longitudinal, circumferential as well as radial systolic strain were determined in all patients utilizing a commercially available CT strain software.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Moreover, it should be remembered that the peak strain values are underestimated in the computed tomography assessment in relation to the echocardiographic assessment. In the recently published literature standardizing the CT-derived myocardial strain measurement, it has been shown that computed tomography significantly underestimates the strain values relative to echocardiographic assessment [ 11 ]. Ammon et al showed that the highest predictive accuracy for the echocardiographic GLS < 18% criterion is characterized by the computed tomography-derived GLS < 12% criterion [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it should be remembered that the peak strain values are underestimated in the computed tomography assessment in relation to the echocardiographic assessment. In the recently published literature standardizing the CT-derived myocardial strain measurement, it has been shown that computed tomography significantly underestimates the strain values relative to echocardiographic assessment [ 11 ]. Ammon et al showed that the highest predictive accuracy for the echocardiographic GLS < 18% criterion is characterized by the computed tomography-derived GLS < 12% criterion [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strain can be assessed by echocardiography (ECHO) and have a utility in prognosing patients with coronary artery disease (CAD), mitral stenosis, and other cardiac diseases [ 8 ]. Next to ECHO, it is possible to measure strain using magnetic resonance imaging (MRI) [ 9 ] and computed tomography (CT) [ 10 , 11 ]. Global longitudinal strain (GLS) has better prognostic value in predicting adverse cardiac events than left ventricular ejection fraction (LVEF) measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published approach employed a spatial-sequential network with bi-directional learning of 4D CT images which out-performed existing approaches for automated LV segmentation ( 40 ). Currently, there are commercially available programs for calculation of regional myocardial strain from contrast cine CT but these are based on 2D analysis of stacks of images ( 41 ). Although CT imaging holds promise for true high-resolution 3D analysis of regional myocardial strain, to date CT derived strain has not yet been assessed as a tool for the early prediction of AIC.…”
Section: Evaluation Of Left Ventricular Systolic Function and Strain:...mentioning
confidence: 99%
“…Previous studies have used 4DCT to estimate LV myocardial function. [17][18][19][20][21] Lamash et al used a deformable LV model to estimate regional and global myocardial strains from 3D velocity fields which were extracted via a novel optical flow technique. 17 The model was then used to successfully differentiate between normal and abnormal myocardial segments in a cohort of 93 subjects with cardiac 4DCT scans.…”
Section: Introductionmentioning
confidence: 99%